2020
DOI: 10.3390/app10238463
|View full text |Cite
|
Sign up to set email alerts
|

Biomedical Application of Cyclodextrin Polymers Cross-Linked via Dianhydrides of Carboxylic Acids

Abstract: Cyclodextrin-based nanosponges (CD-NS) are a novel class of polymers cross-linked with a three-dimensional network and can be obtained from cyclodextrins (CD) and pyromellitic dianhydride. Their properties, such as their ability to form an inclusion complex with drugs, can be used in biomedical science, as nanosponges influence stability, toxicity, selectivity, and controlled release. Most pharmaceutical research use CD-NS for the delivery of drugs in cancer treatment. Application of molecular targeting techni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 44 publications
0
15
0
Order By: Relevance
“…A comprehensive review on cyclodextrin-based carriers for delivery of chemotherapeutic cytotoxic anticancer drugs Gonzalez-Gaitano et al (2016) Drug carrier systems based on cyclodextrin supramolecular assemblies and polymers: present and perspectives Mejia-Ariza et al (2017) Cyclodextrin-based supramolecular nanoparticles for biomedical applications Peng et al (2017) Polymeric nanocarriers based on cyclodextrins for drug delivery: host-guest interaction as stimuli responsive linker Adeoye and Cabral-Marques (2017) Cyclodextrin nanosystems in oral drug delivery: A mini review Alvarez-Lorenzo et al (2017) Cyclodextrins as versatile building blocks for regenerative medicine Fenyvesi et al (2019) Applications of steroid drugs entrapped in cyclodextrins Topuz and Uyar (2019) Electrospinning of cyclodextrin functional nanofibres for drug delivery applications Yao et al (2019) Cyclodextrin-based polymer materials: From controlled synthesis to applications Zhang et al (2019) Cyclodextrin-based delivery systems for cancer treatment Ciesielska et al (2020) Biomedical application of cyclodextrin polymers crosslinked via dianhydrides of carboxylic acids Haley et al (2020) Cyclodextrins in drug delivery: applications in gene and combination therapy Qie et al (2020) Advances in cyclodextrin polymers and their applications in biomedicine Seidi et al (2020) Polycyclodextrins: synthesis, functionalization, and applications Tian et al (2020a) Cyclodextrin-based delivery systems for chemotherapeutic anticancer drugs: a review Tian et al (2020b) Cyclodextrin as a magic switch in covalent and non-covalent anticancer drug release systems Wankar et al (2020) Recent advances in host-guest self-assembled cyclodextrin carriers: implications for responsive drug delivery and biomedical engineering Sofiane et al (2020) The use of cyclodextrin or its complexes as a potential treatment against the 2019 novel coronavirus: a mini-review…”
Section: Discussionmentioning
confidence: 99%
“…A comprehensive review on cyclodextrin-based carriers for delivery of chemotherapeutic cytotoxic anticancer drugs Gonzalez-Gaitano et al (2016) Drug carrier systems based on cyclodextrin supramolecular assemblies and polymers: present and perspectives Mejia-Ariza et al (2017) Cyclodextrin-based supramolecular nanoparticles for biomedical applications Peng et al (2017) Polymeric nanocarriers based on cyclodextrins for drug delivery: host-guest interaction as stimuli responsive linker Adeoye and Cabral-Marques (2017) Cyclodextrin nanosystems in oral drug delivery: A mini review Alvarez-Lorenzo et al (2017) Cyclodextrins as versatile building blocks for regenerative medicine Fenyvesi et al (2019) Applications of steroid drugs entrapped in cyclodextrins Topuz and Uyar (2019) Electrospinning of cyclodextrin functional nanofibres for drug delivery applications Yao et al (2019) Cyclodextrin-based polymer materials: From controlled synthesis to applications Zhang et al (2019) Cyclodextrin-based delivery systems for cancer treatment Ciesielska et al (2020) Biomedical application of cyclodextrin polymers crosslinked via dianhydrides of carboxylic acids Haley et al (2020) Cyclodextrins in drug delivery: applications in gene and combination therapy Qie et al (2020) Advances in cyclodextrin polymers and their applications in biomedicine Seidi et al (2020) Polycyclodextrins: synthesis, functionalization, and applications Tian et al (2020a) Cyclodextrin-based delivery systems for chemotherapeutic anticancer drugs: a review Tian et al (2020b) Cyclodextrin as a magic switch in covalent and non-covalent anticancer drug release systems Wankar et al (2020) Recent advances in host-guest self-assembled cyclodextrin carriers: implications for responsive drug delivery and biomedical engineering Sofiane et al (2020) The use of cyclodextrin or its complexes as a potential treatment against the 2019 novel coronavirus: a mini-review…”
Section: Discussionmentioning
confidence: 99%
“…Through the application of ultrasonic vibration, it is possible to promote crosslinking of CD with an appropriate linker, in a certain molar ratio, and in the absence of solvents, thus constituting an environmentally friendly process. Spherical uniform size particles are formed ( Ciesielska et al, 2020 ; Jain et al, 2020 ; Omar et al, 2020 ). The sonication is useful either for the melting or for the solvent condensation method ( Swaminathan et al, 2013 ).…”
Section: Cyclodextrin-based Nanosponges: Synthesis and Propertiesmentioning
confidence: 99%
“…As such, the promotion of reactions by microwave irradiation makes them four times faster than the melting approach ( Andaç et al, 2021 ), and more reproducible and scalable due to uniform and controlled heating provided by microwave irradiation. Thus, using microwave synthesis, it is possible to obtain highly crystalline CDNSs with a narrow particle size distribution ( Ciesielska et al, 2020 ) by reacting CD with an appropriate crosslinker (mostly DPC), using polar aprotic solvents such as DMF ( Anandam and Selvamuthukumar, 2014 ; Zainuddin et al, 2017 ; Sharma et al, 2021 ). As the solvent condensation synthesis can be performed using microwave irradiation, Vasconcelos et al ( Vasconcelos et al, 2016 ) reported the use of tin octanoate catalyst to promote the reaction between βCD and HDI crosslinker using DMF as solvent in a microwave system at 80°C for 30 min.…”
Section: Cyclodextrin-based Nanosponges: Synthesis and Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…At the same time, keeping the amino group significantly improves the solubility of the system used. Therefore, a large group of researchers present CD polymers as compounds with potential medical use [ 10 ]. The presented polymer material can form hydrogels with many known polycations (chitosan, poly- L -lysine) and polyanions (alginic acid, pectin, or hyaluronic acid, etc.)…”
Section: Introductionmentioning
confidence: 99%